(3GdeNJUQ GdfGaY Ch GdfGaY aj eNJUQ GdTQGFYs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj UZQJ aj YXeJg YHGOI GdYGHOjf(B...(3CeG HYO aEfj ehQO aj gPG GdeNJUQ NdGUI GdePgH GdeYJHQ(B...s
(3BNQgG (B:s
(3hGdYUHI ef JbQH ef GdejJ HGdCHhjf hHGdCH cGdCNhGJ hChdGOge hGdYeheI hChdGOge(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B123s
(3GdPQjYI(B:(3L(B20(3,U(B232(3,Qbe(B2636s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis